1870 Idaho Sess. Laws 21 - (:unkn) unknown (My University, 1870)
An Act to Amend an Act Concerning Crimes and Punishment . . ., § 40: Prohibited brandishing any dirk, dirk knife, sword, sword cane, pistol, gun, or other deadly weapon in a rude, angry, and threatening manner.
Keywords: BRANDISHING